Transpersonal Psychology: Altered States of Consciousness, Biofeedback, and Neurotechnology - Valverde, Raul (Bentham Science Publishers, 2022)
Transpersonal psychology is the study of human nature and development that assumes that human beings possess potentials that exceed the limits of ego developed normally. The main goal of transpersonal psychology is to integrate the spiritual experience within a broader understanding of the human psyche and consciousness. Transpersonal Psychology: Altered States of Consciousness, Biofeedback and Neurotechnology introduces the use of biofeedback and neurotechnology for the transpersonal therapist to induce and measure altered states of consciousness to deal with persons having mental conditions. The therapist and the patient can benefit from self-exploration and self-realization of altered consciousness that could be responsible for the mental condition of the patient. Chapters in the book start with an introduction to the theory of consciousness and transpersonal psychology followed by an explanation of the relationship of quantum physics to consciousness model. The book then progresses towards in depth topics such as biofeedback which covers the measurement parameters for understanding consciousness and computer-based technologies that help induce altered states of consciousness. Finally, the book concludes by linking all the concepts together to guide the transpersonal psychologist to measure and support transpersonal psychotherapy through a cybertherapy system. Transpersonal Psychology: Altered States of Consciousness, Biofeedback and Neurotechnology is an ideal guide for the transpersonal psychologist and psychotherapist and the enthusiast who wants to understand the science behind altered states of consciousness from a theoretical and experimental framework.